Heavy metals removal by thiol modified oak charcoal: adsorption efficiency and selectivity - Zeinab Ezzeddine; Batoul Solh; Hussein Hamad (Institute of Advanced Engineering and Science, 2021)
Herein, the removal of heavy metals on thiol modified oak charcoal was investigated. The modified charcoal was characterized by X-ray diffraction, granulometric analysis, and infrared spectroscopy. Then, its adsorption efficiency for the removal of Cd2+, Cu2+, and Pb2+ from water was tested. The effects of several conditions on metals adsorption were investigated such as contact time, pH, electrolytes and the initial metal ions concentration. The adsorption capacities were high (197, 250, and 214 mg g-1 for Cd2+, Pb2+, and Cu2+ respectively). The selectivity was also dependent on the metal ions nature and the functional group used. The mechanism of adsorption is complex where several types of interaction between metal ions and the adsorbent surface are involved.